2000
DOI: 10.5547/issn0195-6574-ej-vol21-no2-2
|View full text |Cite
|
Sign up to set email alerts
|

Where Did the Money Go? The Cost and Performance of the Largest Commercial Sector DSM Programs

Abstract: is an equal opportunity employer. Portions of this document may be illegible in electronic image products. m e s are produced from the best available original d0CUIIWIlL A REPORT FROM THE DATABASE ON ENERGY EFFICIENCY P R O G W S (DEEP)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…These modifications revealed that reported utility DSM spending may be more accurate than Loughran and Kulick claimed, a finding that supports Parfomak and Lave's original conclusions. Qualitative studies confirm the findings made by all three sets of authors that DSM efforts are cost‐effective and have significant potential to decrease electricity prices (Eto et al, 1996, 2000; Nadel, 1992; Nadel & Geller, 1996).…”
Section: Introductionsupporting
confidence: 76%
“…These modifications revealed that reported utility DSM spending may be more accurate than Loughran and Kulick claimed, a finding that supports Parfomak and Lave's original conclusions. Qualitative studies confirm the findings made by all three sets of authors that DSM efforts are cost‐effective and have significant potential to decrease electricity prices (Eto et al, 1996, 2000; Nadel, 1992; Nadel & Geller, 1996).…”
Section: Introductionsupporting
confidence: 76%
“…After the retrofit, energy consumption exceed the model-predicted results by 986 kWh ($84), indicating that the household consumed more electricity in the post-retrofit period. 8 The most widely cited statistical criteria for establishing the acceptability of a baseline consumption model was proposed by Reynolds and Fels [25] who suggest an absolute statistical cutoff criteria: (i) R 2 > 0.7, CV < 7%, or (ii) CV < 12%. Reddy and Claridge [24] have questioned the applicability of absolute measures and proposed a dynamic criterion based on the fractional uncertainty in savings measurement.…”
Section: Example -Negative Energy Savingsmentioning
confidence: 99%
“…Industrial and commercial facilities have evolved standard protocol for evaluating energy conservation programs, primarily because of the large capital expenses involved, but residential programs tend to be subject to less rigorous criteria and performance metrics. For a review of program assessments in commercial facilities, see [7,8]; for residential programs, [15]; for weatherization, [2,4,21].…”
Section: Introductionmentioning
confidence: 99%
“…Critical issue is the following: how much does it cost to save energy through programs that use monetary incentives and targeted information to influence individual customer decisions? For example, [1] presents detailed analysis of the complete costs and measured energy savings from the largest commercial sector DSM programs operated by U.S. electric utilities. The programs, as a whole, have been found as cost effective.…”
Section: Introductionmentioning
confidence: 99%